"A Powerful Visual Statement": Race, Class, and Gender in Uniform and Dress Code Policies in New Orleans Public Charter Schools. Issue 1 (February 2022) - Knipp, Hannah; Stevenson, Rae
The current study critically analyzes the dress code and uniform policies of 89 New Orleans public charter schools using content analysis. Dress code and uniform policies across the United States are deeply rooted in racism, sexism, and classism and, through their implementation, further contribute to these same oppressions. In this study, the dress code and uniform policies, including the justifications for policy, specific policy rules, and possible consequences for noncompliance, are the primary units of analysis. Drawing on intersectionality and the concept of misogynoir, this study attempts to dissect what school policies communicate about race, class, and gender. The racist, classist, and sexist language deployed within the policies is exposed while specifically centering the disproportionate regulation of young black female bodies in dress code policies. School social workers are uniquely positioned to advocate for more equitable dress code and uniform policies. This study contributes to the larger body of literature for its inclusion of data from an entire city as well as its intersectional approach.